Identification of Tropical Marine Diatom Chaetoceros dayaensis CBO from Bokor Island through Morphology and Genetic Marker Analysis - Stiawan, Elva; Sutomo, Sutomo; Sapulete, Sherly; Nurachman, Zeily; Rachmayanti, Yanti (Indonesian Journal of Chemical Studies, 2022)
Microalgae are well-recognized by many researchers working on bioenergy resources due to its capability to produce high amounts of lipids as biodiesel precursors. Diatoms as a group of microalgae that specifically categorized by their silica valve could be more attractive to the researchers because in addition to high-lipid content, their silica features can be also utilized for wider applications, or used for diatoms bioproduct purification. Identification of some diatom species, such as the diatom genus Chaetoceros, as an initial step in diatom studies were difficult to accurately perform because of the unique morphology of silica frustules. Meanwhile, some candidate universal genetic markers of microalgae could also be used for the identification of diatoms with brittle frustules. In this research, we aimed to identify isolate CBO of tropical marine Chaetoceros CBO strain using morphological and genetic approaches. The isolate CBO of Chaetoceros sp. CBO was successfully obtained from sea region of Bokor Island, Kepulauan Seribu, Jakarta, and cultivated in our laboratory as culture stock for further use. Better resolution of the Chaetoceros CBO identification until species level was shown by genetic analysis toward two proposed gene markers for microalgae (rbcL-3P and V4 region of 18S rDNA) rather than by morphological. Specific DNA region for this specimen was found in V4 region of 18S rDNA genetic marker that could be recognized by MspA1I restriction enzyme. Hence, the RFLP (restriction fragment length polymorphism) method could be also used as an initial diagnostic tool for identification of this tropical marine Chaetoceros dayaensis CBO and for stock culture labelling purposes.